The Influence of Social Marketing on Purchasing Decisions for Bika Ambon Zulaikha Medan City - Tio Annisa Putri Tanjung; Badaruddin; Bisru Hafi; Sismudjito; Ilham Saladin (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
This research discusses how to find out whether there is an influence of social marketing on purchasing decisions for Bika Ambon Zulaikha, Medan City. Ideas and habits are products that are marketed. Social products in the form of beliefs, attitudes and values. In analyzing the research using social marketing theory by Philip Kotler and Edvardo Roberto. This research uses a descriptive method with a quantitative approach. Data collection techniques were carried out using questionnaires and documentation. Based on the results of descriptive analysis and interpretation of data in the form of descriptions or narrative sentences, it explains that the variables of social marketing are belief, attitude, and value as well as customer satisfaction, product, service, and location with analysis using Philip Kotler and Edvardo Roberto assisted by Protestant Ethics and Spirit. Capitalism by Max Weber. The results of this research are that social marketing (X) on cutomer satisfaction for Bika Ambon Zulaikha (Y) is 45.2%, while 54.8% of Bika Ambon Zulaikha customer satisfaction are influenced by other variables.